Functional limitations in upper extremity and its impact on QOL among post-mastectomy females in Peshawar: a cross-sectional study - Khan, Mishal; Hassan, Tashbeeh; Bibi, Sana; Chauhan, Sharna; Syeda Afsheen Hasnain Daud,; Syed Muhammad Shabbir Ali Naqvi, (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the prevalence of functional limitations in the upper extremity among post-mastectomy patients, and to assess its impact on quality of life. Method: The prospective, analytical, cross-sectional study was conducted at Hayatabad Medical Complex and Khyber Teaching Hospital, Peshawar, Pakistan, from June to October 2023, and comprised female patients aged at least 18 year who had undergone unilateral mastectomy 3 months before data collection. The impact of demographic variables age, occupation and residence on functional limitations in the upper extremities was explored using the Quick Disabilities of Arm, Shoulder and Hand and Functional Assessment of Cancer Therapy-Breast questionnaires. Data was analysed using SPSS 25. Results: Of the 123 female, married patients, 31(25.25%) were aged 51-60 years, 3(2.4%) were aged 18-30 years, 75(61%) were living in rural areas, and 103(83.7%) were housewives. Overall, 64(52%) females showed no limitations, 50(40.65%) showed mild, and 9(7.32%) showed moderate functional limitations in the upper extremities. The variation in the quality of life among different functional limitation categories post-mastectomy was not significant (p=0.061). There was no significant association of age (p=0.784), residence (p=0.442) and occupation (p=0.387) with functional limitations in the upper extremities. Conclusion: Upper extremity functional limitations were not significantly associated with a decline in quality of life among breast cancer survivors. Key Words: Mastectomy, Quality of life, Post-mastectomy, Functional limitation, Upper extremity.